Returns to Education in the Russian Federation : Towards Evidence Based Decision Making with Fiscal and Private Returns to Education - Melianova, Ekaterina; Parandekar, Suhas; Volgin, Artem (World Bank, Washington, DC, 2020)
This paper used institution level information about graduate earnings and estimates of fiscal and private costs to obtain fiscal and private returns to education using an internal rate of return calculation. As data has been collected so far only on earnings trajectories for three years following graduation, these are not lifetime returns, but they are adequate to provide relative estimates. Samara Energy College with private returns of 35 percent and fiscal returns of 13 percent leads the list of colleges. V.R. Fillipova Buryat State Agricultural Academy in Ulan Ude leads the universities list with private returns of 9 percent and fiscal return of 7 percent. Even though only preliminary results are presented here, the data length and model sophistication can only grow in the future. The resulting information on returns to investment will serve government stakeholders as well as individual students.